Infinite speed behavior of two-temperature Green–Lindsay thermoelasticity theory under temperature-dependent thermal conductivity - Kumar A.; Shivay O.N.; Mukhopadhyay S. (My University, 2025)
The present work attempts to analyze the effects of temperature-dependent thermal conductivity on thermoelastic interactions in a medium with a spherical cavity under two-temperature Green–Lindsay thermoelasticity theory. An attempt is made to compare the results with the corresponding results under other three thermoelastic models. The thermal conductivity of the material is assumed to be depending affinely on the conductive temperature. It is assumed that the conductive temperature is prescribed at the stress-free boundary of the spherical cavity. Assuming spherical symmetry motion, the resulting thermoelastic system in one space dimension is solved by using the Kirchhoff transformation, Laplace transform technique and expansion in modified Bessel functions. The paper concludes with numerical results on the solution of the problem for specific parameter choices. Various graphs depict the behavior of the conductive and thermodynamic temperature, the displacement and two nonzero components of stress. A detailed analysis of the results is given by showing the effects of the assumed temperature dependence of the material property. The effect of employing the two-temperature model is discussed in detail. We observe an infinite domain of influence under the two-temperature model as compared to the classical Green–Lindsay model, which we hope will be a useful insight. © 2019, Springer Nature Switzerland AG.